Potential Incompatibility Problem of Intravenous Drugs’ Administration among Intensive Care Unit (ICU) Patients at PKU Muhammadiyah Yogyakarta Hospital - Ardhanarishwari Umi Salamah; Fita Rahmawati; Fivy Kurniawati (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Drugs’ administration among hospitalized patients in ICU commonly is given intravenously. Mixing the intravenous drugs may result in incompatibility problem that might affect the drugs’ stability and bioavailability. The aim of the study was to investigate the potential incompatibility problem of  intravenous mixing drugs’ administration among ICU patients at PKU Muhammadiyah Yogyakarta Hospital. This study was a cross-sectional study in which design and data was obtained from ICU patients’ medical record retrospectively with purposive sampling in order to observe the pattern of intravenous drug’s combination. The potential incompatibility problem was analyzed using Handbook on Injectable Drugs. There were 79 out of 119 medical records which fulfilled sample inclusion criteria taken in this study. Parenteral dosage form was commonly used rather than non parenteral (62.06%) among ICUs’ patients. The potential incompatibility pattern consisted of incompatibility of intravenous drugs, electrolyte solutions/parenteral nutritions in mixture form, and the electrolyte solutions/parenteral nutritions, which are administrated simultaneously. Potential incompatibility of intravenous dosage was found in 50 events out of 79 patients (0.63 events per patients), which consisted of 8 events (8.51%) in using of drugs administrated simultaneously, 10 events (19.23%) in using of electrolyte solutions/parenteral nutritions in mixture form, and 32 events (11.72%) in using of electrolyte solutions/parenteral nutritions administrated simultaneously. Common potential incompatibilities types were precipitation of drugs and drug’s adsorption to packaging materials.